GABAergic dysfunction in pediatric neuro-developmental disorders - Smith-Hicks, Constance L. (Frontiers in Cellular Neuroscience, 2013)
The GABAergic system is central to the development and functional maturation of the nervous system. Emerging evidence support the role of GABAergic dysfunction in neuro-developmental disorders. This review presents the molecules and mechanisms that underlie GABA system dysfunction in several neuro-developmental disorders presenting in childhood. The impact on synaptic plasticity, neuronal circuit function and behavior, followed by targeted treatment strategies are discussed.